The Historical Jesus Quest : A Foundational Anthology - Dawes, Gregory W., (Tools for Biblical Study, 1999)
Scholars and students have long awaited such a volume, which provides direct access to the classic writers on the Historical Jesus, allowing them to speak in their own words. This volume brings together, in English translation, substantial extracts from the key works in Jesus studies. Includes substantial quotations in English from Troeltsch, Schweitzer, Wrede, Kähler, Bultmann, Käsemann and others. The selections are accompanied by brief introductions to each writer with helpful summaries of the works from which extracts are taken.